Brevibacterium Bacteremia in the Setting of Pyogenic Liver Abscess: A Case Report with Accompanying Literature Review - Sarah Hossain; Afif Hossain; Aldo Barajas-Ochoa; Michael A. Jaker (Case Reports in Infectious Diseases)
A 71-year-old Pakistani man with poorly controlled type 2 diabetes mellitus presenting with worsening mental status, abdominal pain, and oral intake for the past seven days was found to have pyogenic hepatic abscess with unculturable bacteria and subsequently found to have rare Brevibacterium bacteremia.